The Migration Policy during Covid-19 Outbreak: The Case of Indonesia’s Immigration Governance - Arifin, Ridwan; Wiraputra, Anindito (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2020)
This paper discusses the case of immigration governance, responding to the Indonesian migration policy during the Covid-19 outbreak. It indicates the immigration policy in Indonesia has quickly changed every month, which becomes serious issues, for example, about overlapped authorities at borders, fragmented policy, border law enforcement disputes, and confusion about visa and residence permits policy. This paper applies the qualitative research methodology of a single case study with a theoretical framework approach. The study finds the migration policy and governance in Indonesia in the Covid-19 pandemic have incorporated the theory of governance with five propositions as described in Stoker (1998). However, the responsibility of cross-border station closure is blurred, which indicates no coordination among border agencies, and this may lead to blaming and scapegoating. The immigration policy at Indonesia’s borders illustrates a rigorous policymaking process but inconsistency where the policy instruments were revised and extended every month. The policy has not been designed for the situation after the Covid-19 crisis in Indonesia is declared over by the competent authority. This paper proposed the concept of integrated border management (IBM), policy formulation stages, and adoption of technology.